Fate of Central Venous Catheters Used for Acute Extracorporeal Treatment in Critically Ill Pediatric Patients: A Single Center Experience. Issue 3 (June 2016) - Rus, Rina R; Premru, Vladimir; Novljan, Gregor; Grošelj‐Grenc, Mojca; Ponikvar, Rafael
Abstract: Renal replacement treatment (RRT) is required in severe acute kidney injury, and a functioning central venous catheter (CVC) is crucial. Twenty‐eight children younger than 16 years have been treated at the University Medical Centre Ljubljana between 2003 and 2012 with either acute hemodialysis (HD) and/or plasma exchange (PE), and were included in our study. The age of the patients ranged from 2 days to 14.1 years. Sixty‐six CVCs were inserted (52% de novo, 48% guide wire). The sites of insertion were the jugular vein in 20% and the femoral vein in 80%. Catheters were in function from 1 day to 27 days. The most common cause for CVC removal or exchange was catheter dysfunction (50%). CVCs were mostly inserted in the femoral vein, which is the preferred site of insertion in acute HD/PE because of the smaller number of complications.